Experimental study on fatigue crack growth of QSTE420TM steel with a single dwell-overload and a combined prediction model. (July 2021) - Gong, Hao; Lu, Yun-chao; Yang, Feng-peng; Chen, Te
Abstract: To study the fatigue crack behaviors of QSTE420TM steel under constant amplitude with a single dwell-overload, a series of experiments are performed. The dwell time changed from 0 s to 10 6 s. The result shows that the dwell-overload retardation is more distinct than the single overload. The retardation degree is not proportional with the dwell time, its greatest level appears when the dwell time lasted 10 4 s, then it gradually becomes stable. A combined model, which considers the effects of both residual stress and crack closure, is proposed by introducing a dwell factor to describe the plastic zone at the crack tip. Graphical abstract: Unlabelled Image Highlights: The tests were conducted on QSTE420TM steel with a single dwell-overload. The retardation phenomenon under dwell-overload is more obvious than overload. A time-dependent model considering the residual stress effect and crack closure effect was proposed. The model is able to predict fatigue crack growth rates and lifetimes well.